2020
DOI: 10.1212/wnl.0000000000008867
|View full text |Cite
|
Sign up to set email alerts
|

Unique white matter structural connectivity in early-stage drug-naive Parkinson disease

Abstract: ObjectiveTo investigate the topographic arrangement and strength of whole-brain white matter (WM) structural connectivity in patients with early-stage drug-naive Parkinson disease (PD).MethodsWe employed a model-free data-driven approach for computing whole-brain WM topologic arrangement and connectivity strength between brain regions by utilizing diffusion MRI of 70 participants with early-stage drug-naive PD and 41 healthy controls. Subsequently, we generated a novel group-specific WM anatomical network by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 35 publications
(45 reference statements)
2
45
0
Order By: Relevance
“…Considering the use of whole-brain analysis, these results support the hypothesis that widespread neuropathology exists at the time of clinical onset, possibly driven by the inclusion of GM in whole-brain analysis. Connectome analysis has also shown significant differences in the WMderived structural connectome associated with PD (29,30,105). More specifically, lower global efficiency and global clustering coefficient have been observed in PD compared with HCs (26).…”
Section: Dti In Early-stage Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the use of whole-brain analysis, these results support the hypothesis that widespread neuropathology exists at the time of clinical onset, possibly driven by the inclusion of GM in whole-brain analysis. Connectome analysis has also shown significant differences in the WMderived structural connectome associated with PD (29,30,105). More specifically, lower global efficiency and global clustering coefficient have been observed in PD compared with HCs (26).…”
Section: Dti In Early-stage Pdmentioning
confidence: 99%
“…Finally, Tinaz et al (28) investigated the structural and functional organization in PD subjects, finding reduced WM connectivity in frontoparietal-striatal nodes compared to controls, but no change in modular organization of the WM tracts. A recent study by Mishra et al (105) reported that there is an early-stage PD-specific WM-derived connectome comprising pathophysiologically relevant regions and that the overall connectivity in early-stage PD in these regions is significantly higher than that compared to HC. Additionally, PD groups have shown reduction in functional local network metrics in many nodes distributed across the connectome (28).…”
Section: Dti In Early-stage Pdmentioning
confidence: 99%
“…has 'small-world' organization (Watts and Strogatz 1998), which facilitates the efficient segregation and integration of complex networks with low energy and wiring costs (Rubinov and Sporns 2010;Liao et al 2017). Using noninvasive neuroimaging, graph theoretical analysis has revealed PD-related disconnection patterns in both functional (Suo et al 2017;Berman et al 2016;Sang et al 2015;Luo et al 2015;Fang et al 2017;Ma et al 2017b;Gottlich et al 2013;Vancea et al 2019) and structural white matter networks (Galantucci et al 2017;Shah et al 2017;Kamagata et al 2018;Tinaz et al 2017;Aarabi et al 2015;Wen et al 2017a, b;Nigro et al 2016;Abbasi et al 2018;Mishra et al 2020). However, little is known about whether PD disrupts the topological organization of grey matter (GM) morphological networks.…”
Section: Introductionmentioning
confidence: 99%
“…For PD in particular, which has largely been considered a grey matter disease, the role of myelin still is under active debate in the field. While reports generally agree that changes occur in white matter structure as the disease progresses [32][33][34][35], they contradict with respect to presumed consequences. On one hand, some studies interpret microstructural changes that are typical for neurodegeneration to reflect loss of white matter due to demyelination and axonal damage [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%